Coligand role in the NHC nickel catalyzed C–F bond activation: investigations on the insertion of bis(NHC) nickel into the C–F bond of hexafluorobenzene. Issue 40 (14th October 2020) - Kuntze-Fechner, Maximilian W.; Verplancke, Hendrik; Tendera, Lukas; Diefenbach, Martin; Krummenacher, Ivo; Braunschweig, Holger; Marder, Todd B.; Holthausen, Max C.; Radius, Udo
Abstract : A combined experimental and theoretical study on the mechanism of the C–F bond activation of C6 F6 with [Ni(NHC)2 ] is provided. Abstract : The reaction of [Ni(Mes2 Im)2 ] (1 ) (Mes2 Im = 1, 3-dimesityl-imidazolin-2-ylidene) with polyfluorinated arenes as well as mechanistic investigations concerning the insertion of 1 and [Ni( i Pr2 Im)2 ] (1 ipr ) ( i Pr2 Im = 1, 3-diisopropyl-imidazolin-2-ylidene) into the C–F bond of C6 F6 is reported. The reaction of 1 with different fluoroaromatics leads to formation of the nickel fluoroaryl fluoride complexes trans -[Ni(Mes2 Im)2 (F)(Ar F )] (Ar F = 4-CF3 -C6 F4 2, C6 F5 3, 2, 3, 5, 6-C6 F4 N 4, 2, 3, 5, 6-C6 F4 H 5, 2, 3, 5-C6 F3 H2 6, 3, 5-C6 F2 H3 7 ) in fair to good yields with the exception of the formation of the pentafluorophenyl complex 3 (less than 20%). Radical species and other diamagnetic side products were detected for the reaction of 1 with C6 F6, in line with a radical pathway for the C–F bond activation step using 1 . The difluoride complex trans -[Ni(Mes2 Im)2 (F)2 ] (9 ), the bis(aryl) complex trans -[Ni(Mes2 Im)2 (C6 F5 )2 ] (15 ), the structurally characterized nickel(i ) complex trans -[Ni I (Mes2 Im)2 (C6 F5 )] (11 ) and the metal radical trans -[Ni I (Mes2 Im)2 (F)] (12 ) were identified. Complex 11, and related [Ni I (Mes2 Im)2 (2, 3, 5, 6-C6 F4 H)] (13 ) and [Ni I (Mes2 Im)2 (2, 3, 5-C6 F3 H2 )] (14 ), were synthesized independently by reaction of trans -[Ni(Mes2 Im)2 (F)(Ar F )] with PhSiH3 . Simple electron transfer from 1 to C6 F6 was excluded, as the redox potentials of the reaction partners do not match and [Ni(Mes2 Im)2 ] +, which was prepared independently, was not detected. DFT calculations were performed on the insertion of [Ni( i Pr2 Im)2 ] (1 ipr ) and [Ni(Mes2 Im)2 ] (1 ) into the C–F bond of C6 F6 . For 1 ipr, concerted and NHC-assisted pathways were identified as having the lowest kinetic barriers, whereas for 1, a radical mechanism with fluoride abstraction and an NHC-assisted pathway are both associated with almost the same kinetic barrier.